Revitalization of Fisherman and Rural Economy For Acceleration of Poverty Reduction In The Digital Era: Roots of Problems and Solutions - Andi Cahaya (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2022)
The results of this normative research article are the contents of the inaugural speech by Professor Dr. Dra. Andi Cahaya, M.Sc., who discussed